Obtaining and characterization of stilbene polycrystals for detection of charged particles - Tarasov, V.; Andryushchenko, L.; Vlasova, I.; Shlyakhturov, V.; Shpilinskaya, O.; Trefilova, L.; Rybka, E. (Functional Materials, 2018)
Stilbene polycrystals with improved energy resolution were obtained by technique of hot vacuum pressing of plate-shape crystallites grown by crystallization from saturated solution of stilbene powder in dichloro-ethane. Transparency and scintillation parameters of the stilbene polycrystals were found to depend on the duration of keeping the initial material under vacuum before pressing. In comparison with 8.2 % energy resolution of the stilbene single crystal, the stilbene polycrystal has 8.8 % energy resolution under 624 keV electrons, whereas under 5.5 MeV α-particles, both the stilbene poly- and single crystals have 11.9 % energy resolution.